Bifunctional Passivation through Fluoride Treatment for Highly Efficient and Stable Perovskite Solar Cells. Issue 30 (26th June 2022) - Liu, Chang; Zhang, Jiyao; Zhang, Luozheng; Zhou, Xianyong; Liu, Yanliang; Wang, Xingzhu; Xu, Baomin
Abstract: Due to the low formation energy, surface defects are more likely to form on the surface of TiO2 films, resulting in a decline in the efficiency and stability of perovskite solar cells (PSCs). Additionally, defects on the bottom surface of the perovskite layer in contact with TiO2 play a key role in V oc (open circuit voltage) loss and the PSC degradation process. Therefore, to improve the efficiency and stability of PSCs, it is critical to develop a reproducible and low‐cost method for passivating the defects on both the TiO2 surface and on the bottom surface of the perovskite layer. In this work, fluoride is utilized as a bifacial contact passivation agent for decreasing the number of defects on the TiO2 surface and the bottom surface of the perovskite layer. PSC efficiency can be significantly increased from 21.3% to 23.7% with fluoride passivation. In addition, the long‐term stability of PSCs, especially light irradiation stability, can be markedly improved. The passivation effects of fluoride treatment on TiO2 films are studied by theoretical calculation and experimental characterization. This work provides a thorough understanding of the TiO2 /perovskite interface and demonstrates an approach for improving the efficiency and stability of PSCs. Abstract : To enhance the efficiency and stability of perovskite solar cells (PSCs), a bifunctional strategy for simultaneously passivating defects in both the TiO2 and the perovskite layer with fluoride passivation is developed. The PSC efficiency can be significantly increased from 21.3% to 23.7%. Moreover, the long‐term stability of PSCs, including humidity, light, and thermal stability, can be significantly improved.